Developing machine training (DBH 2MCS) to improve beginner athlete service in Sepak Takraw in sumedang regency - Hermawan, Dadang Budi; Asmawi, Moch; Tangkudung, James (Journal of Education, Health and Sport, 2019)
The use of technology in sport can be seen as an assisting tool to support and improve athletes’ performance quality. In sepak takraw sport, there is a need to improve athlete’ skill and achievement in terms of service drill practice. This study is aimed at : (1) designing a ball conveyor (DBH 2MCS) machine to facilitate beginner athlete service drills in sepak takraw (2) producing an effective ball conveyor (DBH 2MCS) for beginner athlete service drill . To achieve the objectives of the study, research and development was applied. The results of this study show that the (DBS 2MCS) machine was effective to improve athlete service capability in sepak takraw. In line with this, several evaluation from experts to assess the machine were gathered. Assessment I in terms of material, expert rated the machine "Very Good" with a score of 84. Assessment II conducted by coach, the machine was considered "Very Good" with a score of 87. Assessment III, in terms of machinery, the expert valued it "Very Good" with a score of 89. The conclusions of this study are (1) Sepak takraw conductor (DBS 2MCS) machine can be used to facilitate athlete service drill for beginners, (2) the machine is effective as a tool to improve athlete service drill for beginners. The machine is recommended to be used to help beginner athlete improve their service training in sepak takraw.